SOCIAL CONFLICT IN THE NOVEL SANGKAKALA DI LANGIT ANDALUSIA BY HANUM SALSABILA AND RANGGA ALMAHENDRA - Hasanah, Ummi; Said, Moch; Zawawi, Moh (Annual International Conferences on Language, Literature, and Media, 2023)
Social Conflict is a human problem that will always occur and bring change. George Simmel argues that the concept of social Conflict that occurs in society is the source of civilization. This study aims to (1) describe the forms and causes of social Conflict in the novel Sangkakala di Langit Andalusia by Hanum Salsabiela Rais and Rangga Almahendra based on George Simmel's perspective; (2) describe the resolution of social Conflict in the novel Sangkakala di Langit Andalusia by Hanum Salsabiela Rais and Rangga Almahendra based on George Simmel's perspective. This type of research is a literary criticism. The data collection technique uses reading and note-taking techniques. Data analysis uses the Miles Huberman analysis model: reduction, presentation, and conclusion drawing. The results showed that social Conflict in the novel Sangkakala di Langit Andalusia by Hanum Salsabiela Rais and Rangga Almahendra based on George Simmel's perspective consists of: (1) three types of social Conflict, namely: a. Conflict between individuals with three forms of social Conflict, namely sarcasm, debate, and tension; b. Conflict between individuals and groups with one form of Conflict, namely tension; and c. Conflict between groups and individuals with two forms of Conflict, namely bullying and oppression; (2) four conflict resolutions, tolerance, conciliation, coercion, and arbitration.